Establishment of the neotropicalpredator Amblyseius idaeus(Acari: Phytoseiidae) in Benin, West Africa - Yaninek, John S.; Megevand, B.; Moraes, G.J.; Bakker, F.; Braun, A.; Herren, H.R. (1992)
Populations of the phytoseiid predator Amblyseius(=Neoseiulus) idaeus (Denmark & Muma) From Northeastern Brazil, have been successfully introduced into Benin, West Africa, as part of a classical biological control campaign to control the exotic cassava green mite, Mononychellus tanajoa (Bondar). Monthly follow-up surveys revealed the presence of A. idaeus in most release sites. Some population have persisted for at least 18 months, including two cycles of potentially limiting wet and dry season conditions. In some cities, A. idaeus has been the numerically dominant phytoseiid predator on cassava, Manihot esculenta, where it is associated with the tetranychids M. tanajoa and Oligoncychus gossypii Zacher. During periods of low M.tanajao densities, A. idaeus disappeared from cassava, but were found on weeds with O. gossypii until prey densities on cassava increased.